Liver Injury due to Ashwagandha. A Case Series from Iceland and the U.S. Drug-Induced Liver Injury Network - Björnsson, Helgi K.; Björnsson, Einar S.; Avula, Bharathi; Khan, Ikhlas A.; Jonasson, Jon G.; Ghabril, Marwan; Hayashi, Paul H.; Navarro, Victor (Liver International, 2020)
Background & aims: Ashwagandha (Withania somnifera) is widely used in Indian Ayurvedic medicine. Several dietary supplements containing ashwagandha are marketed in the US and Europe, but only one case of drug-induced liver injury (DILI) due to ashwagandha has been published. The aim of this case series was to describe the clinical phenotype of suspected ashwagandha-induced liver injury. Methods: Five cases of liver injury attributed to ashwagandha-containing supplements were identified; three were collected in Iceland during 2017-2018 and two from the Drug-Induced Liver Injury Network (DILIN) in 2016. Other causes for liver injury were excluded. Causality was assessed using the DILIN structured expert opinion causality approach. Results: Among the five patients, three were males; mean age was 43 years (range 21-62). All patients developed jaundice and symptoms such as nausea, lethargy, pruritus and abdominal discomfort after a latency of 2-12 weeks. Liver injury was cholestatic or mixed (R ratios 1.4-3.3). Pruritus and hyperbilirubinaemia were prolonged (5-20 weeks). No patient developed hepatic failure. Liver tests normalized within 1-5 months in four patients. One patient was lost to follow-up. One biopsy was performed, showing acute cholestatic hepatitis. Chemical analysis confirmed ashwagandha in available supplements; no other toxic compounds were identified. No patient was taking potentially hepatotoxic prescription medications, although four were consuming additional supplements, and in one case, rhodiola was a possible causative agent along with ashwagandha. Conclusions: These cases illustrate the hepatotoxic potential of ashwagandha. Liver injury is typically cholestatic or mixed with severe jaundice and pruritus, but self-limited with liver tests normalizing in 1-5 months.